2003
DOI: 10.1191/1477153503li080oa
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of diffuse daylight due to dust deposition on glazing in a tropical urban environment

Abstract: Transmittance of diffuse daylight by horizontal and vertical glazing was measured in a model placed in an exposed outdoor environment in Singapore for 41 weeks. Correction factors for sensor location were developed, and associations between transmittance and rainfall, wind speed and wind directional frequency were analysed. The paper discusses the interplay of forces for adhesion, resuspension and cleaning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…A dust particle can be removed from a surface by gravitational, vibrational and centrifugal forces, as well as through air currents. 39…”
Section: Cleaning Methods For Daylighting Systemsmentioning
confidence: 99%
“…A dust particle can be removed from a surface by gravitational, vibrational and centrifugal forces, as well as through air currents. 39…”
Section: Cleaning Methods For Daylighting Systemsmentioning
confidence: 99%
“…Dust includes emissions from agriculture and industry, bird droppings, pollen, mineral dust in a dry area, fibers, sand and clay [ 24 ]. Daylight transmission into buildings is affected by the deposition of atmospheric pollutants on glazing [ 25 ]. Even in a clean UK climate, building windows suffer from dust [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For accurate daylight design in a polluted urban area it is important to have appropriate, site-relevant values for the glazing dirt correction factor. Between 1999 and 2003 several field surveys were implemented in the UK and Singapore (Tregenza et al 1999;Sharples et al 2001;Ullah et al 2003) to measure the drop in glazing daylight transmittance due to pollutant depositions in urban buildings. For the British surveys, Tregenza et al (1999) observed an average transmittance reduction of 4-8% for commercial buildings in clean environments, whilst Sharples et al (2001) found that the loss in diffuse transmittance for a vertical window did not usually exceed 10%.…”
Section: Introductionmentioning
confidence: 99%
“…These findings can be used in architectural daylighting calculations for regions environmentally similar to the temperate maritime climate of the UK. Another investigation, in the high-density city of Singapore, which has a tropical humid climate, found a total transmittance reduction ranging from 9% to 36% for vertical and horizontal widows (Ullah et al 2003). In general, Tregenza et al (1999) concluded that the glazing dirt correction factor is related to the particulates in the external atmosphere, precipitation and building form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation